The Regulation and Modification of GSDMD Signaling in Diseases - Li, Zihao; Ji, Senlin; Jiang, Mei-Ling; Xu, Yun; Zhang, Cun-Jin (Frontiers in Immunology, 2022)
Gasdermin D (GSDMD) serves as a key executor to trigger pyroptosis and is emerging as an attractive checkpoint in host defense, inflammatory, autoimmune diseases and many other systemic diseases. Although canonical and non-canonical inflammasome mediated classic GSDMD cleavage, GSDMD-NT migration to cell membrane, GSDMD-NT oligomerization, pore-forming have been well recognized, a few unique features of GSDMD in specific condition beyond its classic function, including nonlytic function of GSDMD, the modification and regulating mechanism of GSDMD signaling have also come to great attention and played a crucial role in biological processes and diseases. In the current review, we emphasized the GSDMD protein expression, stabilization, modification, activation, pore formation and repair during pyroptosis, especially the regulation and modification of GSDMD signaling, such as GSDMD complex in polyubiquitination and non-pyroptosis release of IL-1β, ADP-riboxanation, NINJ1 in pore-forming, GSDMD binding protein TRIM21, GSDMD succination and Regulator-Rag-mTOR-ROS regulation of GSDMD, et al. We also discussed the novel therapeutic strategies of targeting GSDMD and summarized recently identified inhibitors with great prospect.